2014
DOI: 10.1007/s00586-014-3553-y
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical discectomy and fusion with ROI-C peek cage: cervical alignment and patient outcomes

Abstract: This is the first prospective study on ROI-C cages. Although this is a preliminary assessment, the ROI-C cage may represent an excellent alternative to other devices or simple bone graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…Biomechanical studies have revealed that the self-locking stand-alone cage provides less stiffness of cervical spine as locking plate does in 2 or 3-level instrumentation [14,15]. But high fusion rate can be achieved using these kinds of cages for the treatment of single-level, double-level, and even three-level cervical spondylopathy (Table 3) [7][8][9][10][16][17][18]. In our study, the nonunion rate was not statistically significant between groups [4.3 % (4/28) vs 7.7 % (2/26)] (P = 0.736).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical studies have revealed that the self-locking stand-alone cage provides less stiffness of cervical spine as locking plate does in 2 or 3-level instrumentation [14,15]. But high fusion rate can be achieved using these kinds of cages for the treatment of single-level, double-level, and even three-level cervical spondylopathy (Table 3) [7][8][9][10][16][17][18]. In our study, the nonunion rate was not statistically significant between groups [4.3 % (4/28) vs 7.7 % (2/26)] (P = 0.736).…”
Section: Discussionmentioning
confidence: 99%
“…The function of anchoring clips is considered to be similar to a plate and screws, offering immediate stabilization after surgery [7]. Studies have also shown that this kind of cages can effectively restore cervical lordosis, and obviate the platerelated complications, as compared to ACDF using cages and plate fixation for single or double-level cervical spondylopathy [7][8][9]. Further, a non-comparative study has reported satisfactory clinical efficacy and radiological outcomes with the three-level ACDF using this kind of PEEK cages [10].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 , 11 ] A ROI-C device (LDR, Troyes, France) of the cervical spine was developed and used clinically in single-level, double-level, or even in multilevel CDDD to overcome these disadvantages. [ 12 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Only after bone fusion can kyphosis and spinal canal stenosis be effectively prevented, so as to prevent compression of spinal cord and nerve root [20] . Wang et al [ 21] and Grasso et al [ 22] reported a fusion rate of 100% in patients with ROI-C who were followed up for 2 years.…”
Section: Discussionmentioning
confidence: 99%